ICSID, public opinion and the effect of (hypothetical) elite messaging - Alexandra Guisinger; Alisha Anderson (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2014)
This Perspective presents a unique survey of American public opinion on ICSID, and via a survey experiment demonstrates that attempts to increase public support by Republicans or Democrats would likely backfire. Only bi-partisan framing of ICSID can positively move public opinion.
Keywords: 330